Femmes militaires dans un contexte d’armée de milice « sans conflit » : quelles logiques d’engagement ? - Stéphanie Monay (Genre & Histoire)
The Swiss Army is still based on a militia system with a compulsory military service for every Swiss male citizen. Swiss women can voluntarily join the army but are still only a very small minority (0,6%). In the context of a « neutral » country where women are not particularly encouraged to join the military units, we are looking to understand the logics of this commitment that can be considered as atypical. After having first explored our quantitative data revealing the rhetorics of motives for this entry into the military world, the use of biographical interviews will allow us to understand more precisely the logics of commitment by mobilizing the concept of gendered socialization and the question of the relationships with sex categories. We will then see that an earlier incorporation of differentiation and hierarchy between genders plays an important part, even if women’s enrollment in the army could be first perceived as a transgression of gender norms.